Influence of Heat Treatment on the Formation of α-Al2O3 Porous Refractory Material from Al(OH)3 - Vu, Hoang Tung; Mai, Van Duong (Old Journal, 2018)
High alumina porous refractory material is one of the materials used in high temperature applications (up to 1700°C). This study uses both aluminum hydroxide as a feedstock for Al2O3 and as a foam agent. When heat treatment, the water in the aluminum hydroxide structure decomposes leaving the porous hole and converting from aluminum hydroxide to the α-Al2O3 crystalline structure. In this study, the use of differential thermal analysis, DTA, DTG to analyze the characteristics of the raw materials. Methods, X-ray diffraction (XRD), photographic scanning electron microscopy (SEM), and some non-standard methods used to analyze the physical properties and structure of materials obtained in the different thermal processing conditions are used to clarify the effect of heat treatment on the structural form of the α-Al2O3 crystalline aggregate and some physical properties of the material.